Respuesta :
-2-3 gives you -5
so then -5 - (-4) gives you -1 and tha'ts your answer
so then -5 - (-4) gives you -1 and tha'ts your answer
The answer is: " -1 " .
_________________________________________________________
Note:
_________________________________________________________
We are given the expresssion:
_________________________________________________________
→ " - 2 − 3 − (−4) " ; & are asked to find the solution to this expression;
→ so we simplify this given expression:
_________________________________________________________
We are only dealing with "subtraction" ; so we go from "left to right", in the order in which they occur; starting with the left.
{Note that the "parentheses" given in this particular problem does not reflect an operation that we are to perform; so we go with the substraction.}.
→ " - 2 − 3 = - 5 " ;
Then:
→ " - 5 − (- 4) = ? " ; ← which is our answer to be solved.
_______________________________________________________
Note:
_______________________________________________________
→ " - 5 − (- 4) = - 5 + 4 " ;
→ {since a "negative minus a negative is a postive" }.
→ {that is; "subtracting a negative" is "adding a positive" .}.
_______________________________________________________
And we have:
_______________________________________________________
→ " - 5 + 4 = - 1 " .
_______________________________________________________
The answer is: " -1 " .
_______________________________________________________
_________________________________________________________
Note:
_________________________________________________________
We are given the expresssion:
_________________________________________________________
→ " - 2 − 3 − (−4) " ; & are asked to find the solution to this expression;
→ so we simplify this given expression:
_________________________________________________________
We are only dealing with "subtraction" ; so we go from "left to right", in the order in which they occur; starting with the left.
{Note that the "parentheses" given in this particular problem does not reflect an operation that we are to perform; so we go with the substraction.}.
→ " - 2 − 3 = - 5 " ;
Then:
→ " - 5 − (- 4) = ? " ; ← which is our answer to be solved.
_______________________________________________________
Note:
_______________________________________________________
→ " - 5 − (- 4) = - 5 + 4 " ;
→ {since a "negative minus a negative is a postive" }.
→ {that is; "subtracting a negative" is "adding a positive" .}.
_______________________________________________________
And we have:
_______________________________________________________
→ " - 5 + 4 = - 1 " .
_______________________________________________________
The answer is: " -1 " .
_______________________________________________________